Mengkategorikan Resiko Kecelakaan Kerja Konstruksi Pada Proyek Pembangunan Pasar Pon Kabupaten Trenggalek Menggunakan Matriks Penilaian Resiko - Rina Nurmala; Suwarno Suwarno; Mochammad Zaenuri Arifin (Faculty of Engineering, Kadiri University, 2021)
Construction work accidents become part of construction activities that need to be considered. Work accidents cause considerable losses so that there needs to be proper management of the work safety system. Definition of the risks that occur in construction activities can be done to reduce losses incurred. This research aims to categorize the risk of work accidents that occur in the Trenggalek Regency Pon Market development project. Categorize is done using the risk assessment matrix according to AS /NZS 4360:2004 so that the risk grouping category is obtained. Research methods use quantitative descriptive. The research population of 100 workers consisting of team leaders, architectural experts, structural civil experts, mechanical experts, experts, drafters, project administration, supervisors, artisans and workers with a total of 50 respondents. Data collection is done by distributing questionnaires to respondents. From the results of the questionnaire conducted validity testing and reliability test using IBMSPSS Statistic software. The results of the study obtained the risks that occurred categorized at low and medium levels. At the medium level probability with a scale often occurs that is the type of wound on the limbs. While probability with scale can occur at any time, namely the type of injury on the hand. So that from these results, risk control can be done and what things must be done to avoid work accidents in the Trenggalek Regency Pon Market development project.